Answer:
6
Step-by-step explanation:
Answer:
3x + 2x2 + 4 = 5
3x + 2x2 + 4 – 5 = 5 – 5
First be sure that the right side of the equation is 0. In this case, all you need to do is subtract 5 from both sides.
3x + 2x2 – 1 = 0
2x2 + 3x – 1 = 0
Simplify, and write the terms with the exponent on the variable in descending order.
2x2
+
3x
–
1
=
0
↓
↓
↓
ax2
bx
c
a = 2, b = 3, c = −1
Now that the equation is in standard form, you can read the values of a, b, and c from the coefficients and constant. Note that since the constant 1 is subtracted, c must be negative.
Answer
2x2 + 3x – 1 = 0; a = 2, b = 3, c = −1
Step-by-step explanation:
To find the mean, add up at the numbers and divide by the number of numbers in the set (6)
9 + 4 + 7 + 3 + 10 + 9 =
9 + 11 + 12 + 10
20 + 22
42
42 / 6 = 7
the mean is 7.